2001
DOI: 10.1039/b105374b
|View full text |Cite
|
Sign up to set email alerts
|

Studies related to carba-pyranoses: a strategy for the synthesis of β-1,3-glycosidically linked aminomonocarba-disaccharides

Abstract: The reaction of (E )-1-(2Ј,3Ј,4Ј,6Ј-tetra-O-acetyl-β--glucopyranosyloxy)-3-(trimethylsiloxy)buta-1,3-diene 1 and maleic anhydride gives cycloadduct 10 and ketone 12. Reduction of ketone 13, formed by acidic hydrolysis of silyl enol ether 10, with sodium cyanoborohydride in acetic acid gives an 83 : 17 mixture of the γand δ-lactone 14 and 15. γ-Lactone 14 is transformed into the aminomonocarba-disaccharide, 4-acetamido-2,4-dideoxy-3-O-(β--glucopyranosyl)-5a-carba-β--lyxo-hexopyranose 7, using a five-step pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 15 publications
0
11
0
1
Order By: Relevance
“…The azide unit with its ability to activate the acid group can then be replaced by nucleophiles—as already found by Curtius. Lucente and co‐workers used the synthesis of acyl azides for the preparation of ergopeptides,181 while Larsen and co‐workers prepared β‐1,3‐glycosidically bound aminomonocarbodisaccharides 182…”
Section: Synthesis Of Organic Azidesmentioning
confidence: 99%
“…The azide unit with its ability to activate the acid group can then be replaced by nucleophiles—as already found by Curtius. Lucente and co‐workers used the synthesis of acyl azides for the preparation of ergopeptides,181 while Larsen and co‐workers prepared β‐1,3‐glycosidically bound aminomonocarbodisaccharides 182…”
Section: Synthesis Of Organic Azidesmentioning
confidence: 99%
“…Die Azido‐Funktion aktiviert die Säure‐Gruppe, kann aber – wie schon von Curtius gefunden – durch Nucleophile ersetzt werden. Lucente und Mitarbeiter nutzten Acylazide zur Synthese von Ergopeptiden,181 und Larsen und Mitarbeiter stellten β‐1,3‐glycosidisch gebundene Aminomonocarbodisaccharide her 182…”
Section: Synthese Von Organischen Azidenunclassified
“…Larsen et al. had earlier reported the synthesis of bicyclic carbohydrate‐derived [2.2.2]‐lactone 4 from keto anhydride 3 (Scheme A) . Their studies revealed that reduction of the C5‐ketone (red; Scheme A) proceeded with complete diastereoselectivity to afford a single alcohol epimer, which underwent spontaneous 6‐ exo ‐ trig cyclization at the distal carbonyl group of the anhydride (blue; Scheme A).…”
Section: Introductionmentioning
confidence: 99%
“…Larsen et al hade arlier reported the syn-thesis of bicyclic carbohydrate-derived [2.2.2]-lactone 4 from keto anhydride 3 (Scheme 1A). [2][3][4][5] Their studies revealed that reduction of the C5-ketone (red;S cheme 1A)p roceeded with complete diastereoselectivity to afford as ingle alcohole pimer, which underwent spontaneous 6-exo-trig cyclization at the distal carbonyl group of the anhydride (blue;S cheme1A). This approacha ppeared to offer ap lausible synthetic route to bicyclic lactone 5,w hich forms the core of leonuketal (Scheme 1B), through an analogous cyclization reactiono fa lcohol 6,i ft he requisite precursor ketone (7)c ould be secured.…”
Section: Introductionmentioning
confidence: 99%